Diseño de un plan de control de riesgos laborales en las construcciones eléctricas para la Empresa Ingeniería Eléctrica Chugos, ubicada en la ciudad de Ambato. - Palate Pimbo, Wilmer Samuel (2025)
The research, titled "Design of an Occupational Risk Control Plan in Electrical Construction for the Chugos Electrical Engineering Company, located in the city of Ambato," focused on the identification, assessment, and management of occupational risks in the administrative and operational areas. Its justification is that a risk control plan guarantees occupational safety, reduces operating and legal costs, and improves productivity. It also provides applicable knowledge to the electrical sector and serves as a reference for other SMEs. A mixed approach (qualitative and quantitative) was employed, utilizing direct observation, questionnaires, interviews, and documentary analysis, in conjunction with the NTP 330 method, to assess accident risks. The assessment revealed significant deficiencies in infrastructure and safety measures, such as a lack of signage, inadequate structural conditions, and a lack of PPE. The most critical risks included falls from heights, electrical contacts, and entrapment, especially in the positions of linemen and laborers. The assessment classified risks into intervention levels, highlighting the need for urgent action (Level I) for electrical hazards and falls, while others require justified improvements (Level III) or no immediate intervention (Level IV). A risk control plan based on the hierarchy of controls was proposed, concluding that the company must strengthen its safety management, prioritizing critical risks and fostering a preventive culture to reduce workplace incidents and accidents. The importance of proactive intervention and resource allocation to ensure safe working conditions is also emphasized.